Investigating the efficacy of non-thermal plasma in the inactivation of cyanobacteria Dolichospermum sp. - Nguyen Thi My,; Nguyen, Khanh Toan; Pham Le Anh,; Do Hoang Tung,; Nguyen Truong Son,; Doan Thi Oanh,; Nguyen Thi Thu Lien,; Hoang Thi Quynh,; Ngo Thi Diem My,; Le Thi Phuong Quynh,; Nguyen Anh Nguyet,; Pham Phuong Thao,; et al. (Vietnam Journal of Science and Technology, 2024)
Cyanobacteria bloom has been recognized as a serious problem worldwide that requires urgent monitoring and treatment. This study assessed the inactivation of cyanobacteria Dolichospermum sp cells using non-thermal dielectric barrier discharge plasma system under different operational conditions of input wattage and contact time. Both instant and long-term inactivation efficiencies (up to 92.6%) of Dolichospermum sp cells were obtained after plasma treatment regardless the conditions applied. Increased contact time resulted in enhanced inactivation efficiency, while the impact of input wattage was minor. Further investigation was done by analyzing cell morphology, revealing severe deformation of the Dolichospermum sp cell surface due to plasma treatment. The results from this study confirmed the potential of non-thermal plasma in cyanobacteria inactivation which shape the direction for further studies.